Cytokine profile in critically ill patients and/or injured persons with secondary sepsis – influence of different pathogens - Đukić, Snežana; Pavlović, Aleksandar; Ilić, Aleksandra; Božović, Aleksandar; Igrutinović, Gojko; Nikolić, Miljana; Vujačić, Mirjana; Stanojević, Ivan (Vojnosanitetski pregled, 2023)
Background/Aim. The role of the complex sepsis-related immune response has not been fully clarified and remains a subject matter of investigation. Nowadays, sepsis is considered a dynamic syndrome characterized by many, often antagonistic phenomena, ranging from hyperinflammation to anergy and immunoparalysis. The aim of the study was to determine, based on the level of pro- and anti-inflammatory mediators in critically ill patients with secondary sepsis, whether the cytokine profile differs according to the type of bacterial causative agent, as well as to assess the prognostic value regarding the outcome. The outcome measure was in-hospital mortality. Methods. Blood serum samples were taken from 125 critically ill patients admitted to the Surgical Intensive Care Unit with severe secondary sepsis as a consequence of peritonitis, pancreatitis, or trauma. The average age of the patients was 57.7 ± 17.3 years. Of the total number of patients, 84 (67.2%) were males, and 41 (32.8%) were females. The levels of pro-inflammatory interleukin (IL)-1α, IL-1β, IL-6, IL-8, IL-12р70, IL-17А, tumor necrosis factor (TNF)-α, interferon (IFN)-γ, IFN-γ-inducible protein-10 (IP-10), monocyte chemoattractant protein-1(MCP-1), macrophage inflammatory protein (MIP)-1α and MIP-1β, as well as anti-inflammatory mediators IL-4, IL-10, IL-13, IL-27, IL-31, and IL-33, were determined at three time intervals – on the day of admission (the first day) and then on the third and fifth day. The type of the bacterial causative agent was determined using standard microbiological analyses. Results. On the third day of measurement, significant differences in the cytokine levels regarding the nature of bacteremia were determined in all pro- and anti-inflammatory cytokines, except for IL-8. In general, the lowest levels were observed in patients with polymicrobial blood cultures. On the first and fifth days of measurement, no significant differences in the cytokine levels regarding the nature of bacteremia were found. The only significant predictor of the fatal outcome on the first measurement day was IL-17А, Area Under the Receiver Operating Characteristic (ROC) Curve (AUC) of 0.665 (95% confidence interval 0.519–0.791; р = 0.034) in the patients with secondary sepsis as a complication of peritonitis. Conclusion. According to the type of bacterial causative agent, the lowest levels of cytokines have been observed in patients with the polymicrobial blood culture. The low level of IL-17А on the first day of measurement is a good predictor of a fatal outcome in patients with peritonitis as an underlying condition of secondary sepsis. On the other hand, the levels of other cytokines correlated with the outcome only on the fifth day of measurement, and they were higher in survivors than in non-survivors.